2012
DOI: 10.1186/1756-9966-31-56
|View full text |Cite
|
Sign up to set email alerts
|

Functional protease profiling with reporter peptides in serum specimens of colorectal cancer patients: demonstration of its routine diagnostic applicability

Abstract: BackgroundThe progression of many solid tumors is characterized by the release of tumor-associated proteases and the detection of tumor specific proteolytic activity in serum specimens is a promising diagnostic tool in oncology. Here we describe a mass spectrometry-based functional proteomic profiling approach that tracks the ex-vivo degradation of a synthetic endoprotease substrate in serum specimens of colorectal tumor patients.MethodsA reporter peptide (RP) with the amino acid sequence WKPYDAAD was synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
(46 reference statements)
1
12
0
Order By: Relevance
“…The reproducibility of RP spiking was tested with quality control specimens (QCH and QCT) that were randomly interspersed into measurements of serum from tumor patients and controls. The CV was inversely correlated to the concentration of AP [10]. Lowest CV of 5.1% was found in QCT specimens for RP132 with median concentration of 37.0 mol/L (SD 1.9).…”
Section: Reproducibility Of Rp Spikingmentioning
confidence: 90%
See 4 more Smart Citations
“…The reproducibility of RP spiking was tested with quality control specimens (QCH and QCT) that were randomly interspersed into measurements of serum from tumor patients and controls. The CV was inversely correlated to the concentration of AP [10]. Lowest CV of 5.1% was found in QCT specimens for RP132 with median concentration of 37.0 mol/L (SD 1.9).…”
Section: Reproducibility Of Rp Spikingmentioning
confidence: 90%
“…Only five of 144 RPs showed clearly increased cleavage in pooled serum specimens from tumor patients (QCT) when compared to HC (QCH). RP132 has already been validated in previous studies [10,11], whereas RP14, RP46, RP48, and RP83 were newly identified targets for detection of tumor-associated proteolytic activity.…”
Section: Peptide Library Screeningmentioning
confidence: 91%
See 3 more Smart Citations